Durability of Microtensile Bond to Nonetched and Etched Feldspar Ceramic: Self-adhesive Resin Cements vs Conventional Resin - Assuncao Souza, Rodrigo Othavio; Castilho, Anderson A. [UNESP]; Fernandes, Virgilio V. B. [UNESP]; Bottino, Marco Antonio [UNESP]; Valandroe, Luiz Felipe (Quintessence Publishing Co Inc, 2011)
Purpose: The objective of this study was to evaluate the effect of thermocycling (TC), self-adhesive resin cements and surface conditioning on the microtensile bond strength (mu TBS) between feldspathic ceramic blocks and resin cements.Materials and Methods: Fifty-six feldspathic ceramic blocks (10 x 7 x 5 mm) (Vita Mark II) were divided into groups according to the factors "resin cement" (3 cements) and "surface conditioning" (no conditioning or conditioning [10% hydrofluoric acid etching for 5 min + silanization]) (n = 8): group 1: conditioning+Variolink II (control group); group 2: no conditioning+Biscem; group 3: no conditioning+RelyX U100; group 4: no conditioning+Maxcem Elite; group 5: conditioning+Biscem; group 6: conditioning+RelyX U100; group 7: conditioning+Maxcem Elite. The ceramic-cement blocks were sectioned to produce non-trimmed bar specimens (adhered cross-sectional area: 1 +/- 0.1 mm(2)), which were divided into two storage conditions: dry, mu TBS immediately after cutting; TC (12,000x, 5 degrees C/55 degrees C). Statistical significance was deterimined using two-way ANOVA (7 strategies and 2 storage conditions) and the post-hoc Tukey test (p<0.05).Results: Resin cement and thermocycling affected the mu TBS significantly (p = 0.001). In the dry condition, group 5 (18 +/- 6.5 MPa) presented the lowest values of mu TBS when compared to the other groups. TC decreased the mean mu TBS values significantly (p<0.05) for all resin cements tested (9.7 +/- 2.3 to 22.1 +/- 6.3 MPa), except for the resin cement RelyX U100 (22.1 +/- 6.3 MPa). In groups 3 and 4, it was not possible to measure mu TBS, since these groups had 100% pre-test failures during sectioning. Moreover, the same occurred in group 2 after TC, where 100% failure was observed during thermocycling (spontaneous failures).Conclusion: Hydrofluoric acid etching and silanization of the feldspathic ceramic surface are essential for bonding self-adhesive resin cement to a feldspathic ceramic, regardless of the resin cement used. Non-etched ceramic is not recommended.
Keywords: bond strength; feldspathic ceramic; resin cements; ceramic surface treatment; thermocycling